(untitled) - Hornfischer, James D. (New York, 2004)
The story of the Battle of Samar, a naval engagement unlike any other in U.S. history, capturing with unforgettable intensity the men, the strategies, and the sacrifices that turned certain defeat into a legendary victory.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy